Friction ridge analysis in disaster victim identification (DVI): Brazilian case studies - Marco Antonio de Souza; Gabriel de Oliveira Urtiaga; Renata Cristina Grangeiro Ferreira; Luciene Marques da Silva; Jade Kende Gonçalves Umbelino; Flávio Roberto de Melo; Simone de Jesus (Forensic Sciences Research, 2021)
Depending on the magnitude and nature of a disaster, identifying the victims can be a complex task that requires coordinated work by disaster victim identification (DVI) teams based on pre-established protocols. Thus, the analysis of fingerprints has been presented as a method to establish, when possible, the identity of the victims during the DVI process. This study discusses the importance of this primary method of identification and the results obtained in four different disasters in which Brazilian DVI teams were involved: the Air France Flight AF447 plane crash in the Atlantic Ocean, floods and mudslides in the State of Rio de Janeiro, Brazil, the LaMia Flight 2933 plane crash in Colombia, and the tailings dam collapse in Brumadinho, Brazil. Here, we also report the use of the automatic fingerprint capture and identification system, called Alethia, developed by the Federal Police of Brazil and used in the victim identification process in the two latter events mentioned above.Key points • This article presents four different disasters that occurred in Brazil and overseas and involved Brazilian DVI teams in the identification process, focusing on fingerprint identification (Air France Flight AF447, floods and mudslides in the State of Rio de Janeiro, Brazil, LaMia Flight 2933, and the Brumadinho tailings dam collapse). • This article also describes the evolution of the DVI process in Brazil, including a description of the technology currently used by Brazilian fingerprint experts (Alethia). • This article reports how the Alethia System was used in the disasters and how it optimized the human identification process when compared to traditional methods.